Apelin-13 Is an Early Promoter of Cytoskeleton and Tight Junction in Diabetic Macular Edema via PI-3K/Akt and MAPK/Erk Signaling Pathways. (4th April 2018) - Li, Yang; Bai, Yu-jing; Jiang, Yan-rong; Yu, Wen-zhen; Shi, Xuan; Chen, Li; Feng, Jing; Sun, Gui-bo
Abstract : Diabetic macular edema is major cause of vision loss associated with diabetic retinopathy. Breakdown of blood-retinal barrier, especially inner BRB, is an early event in pathogenesis of DR. Apelin, an endogenous ligand of APJ, mediates angiogenesis and is involved in the development of DR. The present study aimed to investigate effects and mechanism of apelin-13 in vascular permeability during DME. We verified apelin-13 was upregulated in DME patients' vitreous. High glucose incubation led to a progressive increase of apelin-13, APJ, cytoskeleton, and tight junction proteins, including VE-Cadherin, FAK, Src, ZO-1, and occludin. Apelin-13 promoted HRMEC proliferation and migration and phosphorylation of both cytoskeleton and tight junction under both normal and high glucose conditions. Besides, apelin-13 activated PI-3K/Akt and MAPK/Erk signaling pathways, including PLC γ 1, p38, Akt, and Erk both in HRMEC and in C57BL/6 mice. Meanwhile, F13A performed opposite effects compared with apelin-13. In in vivo study, apelin-13 was also upregulated in retina of db/db mice. Taken together, apelin-13 increased biologic activity of HRMEC, as well as expression of both cytoskeleton and tight junction in DME via PI-3K/Akt and MAPK/Erk signaling pathways. Apelin-13 as an early promoter of vascular permeability may offer a new perspective strategy in early treatment of DR.